2015
DOI: 10.1097/tp.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success for Pulmonary Rehabilitation in Patients Awaiting Lung Transplantation

Abstract: Short-term comprehensive PR can significantly improve exercise capacity and HRQL in LTx candidates to a clinically relevant extent independent of the underlying lung disease. No relevant predictor influencing PR outcome could be detected. Further research is needed to evaluate the relevance of PR before LTx and its impact on clinical outcome after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 31 publications
3
72
1
Order By: Relevance
“…Firstly, participants with the greatest physical impairments, and thus the largest potential for improvement, dropped out of the study especially in the WBVT group due to several reasons. Literature suggests that typically participants with reduced exercise capacity benefit most from physical training [23]. Gloeckl et al demonstrated a statistically significant improvement following a WBVT intervention (+27 m) using WBVT as a complementary exercise modality on top of conventional endurance and strength training [14].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, participants with the greatest physical impairments, and thus the largest potential for improvement, dropped out of the study especially in the WBVT group due to several reasons. Literature suggests that typically participants with reduced exercise capacity benefit most from physical training [23]. Gloeckl et al demonstrated a statistically significant improvement following a WBVT intervention (+27 m) using WBVT as a complementary exercise modality on top of conventional endurance and strength training [14].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, PR training modalities do not differ between COPD patients with various genotypes. A retrospective analysis indicates that following 3 weeks' inpatient PR training, patients with A1ATD-related COPD improve less in exercise capacity than COPD patients without inherited A1ATD [12]. The reason for this difference remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proven benefits from PR concerning exercise capacity and quality of life [7, 9, 25]. Similarly, in our cohort of more than 1,000 patients awaiting lung transplantation, PR was associated with improvements in 6MWD and all SF-36 domains.…”
Section: Discussionmentioning
confidence: 50%
“…Limited data demonstrate that PR is an effective treatment option for patients on the waiting list for lung transplantation and can improve quality of life and exercise capacity [6, 7]. There is increasing evidence that even patients with most advanced lung disease benefit from PR despite severely impaired functional status [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation